An appetite for research: an interview with Sadaf Farooqi - Sadaf Farooqi (Disease Models & Mechanisms)
Professor Sadaf Farooqi is a clinician and researcher investigating the genetics underpinning obesity. Her research uncovered the first known genes that cause severe obesity, highlighting the significant role of appetite in regulating weight gain. Sadaf's work has been instrumental in proving that many observations in mice are also true in humans, paving the way for novel treatments and shifts in policy. After studying medicine at the University of Birmingham, Birmingham, UK, Sadaf completed her PhD on the genetics of severe childhood obesity at the University of Cambridge, Cambridge, UK, marking the beginning of her impressive research career in this field. She is currently Professor of Metabolism and Medicine at the University of Cambridge and Honorary Consultant in Diabetes and Endocrinology at Addenbrooke's Hospital, Cambridge, UK. Sadaf previously served on the Board of Directors for Disease Models & Mechanisms' publisher, The Company of Biologists. Here, we discuss the fascinating insights from her work on obesity and appetite, her approach to exploring new research questions, and how these discoveries can ultimately impact patients and society.